Naramsin's Year Names Once More. - MARKINA, EKATERINA; WESTENHOLZ, AAGE (Journal of the American Oriental Society)
The article focuses on two tablets from the reign of Naramsin of Akkad, examining their year names and their contribution to understanding the development of Old Akkadian royal iconography. It is reported that despite severe damage to the tablets, the authors utilize fragmentary evidence to reconstruct historical events, particularly Naramsin's dedications to the Temple of Enlil at Nippur and his military victories, including the defeat of Armanum and Ebla.